Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. The reality of applying total quality management at the University of Idlib from the point of view of faculty and administrative academics Mr. Ahmad Mohamad Staif, Co-Prof. Siham Mustafa Abdulaziz, Dr. Hisham Farag Abd Alsid 2. The Commitment of Secondary School Principals in Hodeidah City to Professional Ethics from the Viewpoint of Teachers Mr. Sadiq Abbas Saeed Ahmed, Prof. Abdul-Jabbar Al-Tayeb Ameen 3. Digital transformation and its role in the quality of the educational process for primary school teachers in the city of Riyadh Ms. Rahaf Ali Hamdi, Dr. Saud Ghassan Al-Bishr 4. Ways and Obstacles to Professional Development of English Language Teachers in International Schools in Jeddah: Perspectives of Teachers and Administrators Ms. Maysoon Mohmmed Eid , Dr. Rabab Saleh Alharbi 5. The Degree of Arabic Language Teachers’ Performance in Reinforcing Cooperative and Community Involvement Skills among Secondary Stage Students in Madinah Co-Prof. Mashael Saleh Al-Dosari, Ms. Reem Mahal Al-Ruwaythi 6. The impact of the Item Response Theory (IRT) model on the accuracy of test score equating Dr. Easa Salamah Alhajory, Dr. Mohammed Mahmoud Abdel-Wahab 7. The Situational Leadership Styles of Primary Grades Teachers in Early Childhood Schools according to Hersey and Blanchard’s Theory during the Changes in the Educational Systems Co-Prof. Sama Fouad Khomais, Ms. Rana Hezam Al Sultan